Effect of Audio Tactile Vocabulary (ATV) Media on Reading Difficulties of Children with Specific Learning Disorder in Inclusive Elementary School - Minarsih, Ni Made Marlin; Mahendra, I Ketut (Department of Special Education, 2024)
This research aims to know the effect of Audio Tactile Vocabulary (ATV) media on vocabulary reading ability in children with reading difficulties and with specific learning disorders in inclusive elementary schools—research using a quasi-experimental with quantitative approach. The design is One Group Pretest-Posttest Design—data collection techniques based on interviews, observation, and performance assessment. Data analysis used descriptive statistics. The test results show that the scope of substitution has decreased from 21 wrong vocabulary words to 8 vocabulary words in the scope of omission, and there has been a decrease from 47 wrong vocabulary words to 15 vocabulary words. In the scope of addition, there is also a decrease from 6 to 3 words, and the scope of the perfect shows an increase in vocabulary from 36 to 84.